Chlorophyll Catabolites in Fall Leaves of the Wych Elm Tree Present a Novel Glycosylation Motif - Scherl, Mathias (Chemistry, 2016)
Fall leaves of the common wych elm tree (Ulmus glabra) were studied with respect to chlorophyll catabolites. Over a dozen colorless, non‐fluorescent chlorophyll catabolites (NCCs) and several yellow chlorophyll catabolites (YCCs) were identified tentatively. Three NCC fractions were isolated and their structures were characterized by spectroscopic means. Two of these, Ug‐NCC‐27 and Ug‐NCC‐43, carried a glucopyranosyl appendage. Ug‐NCC‐53, the least polar of these NCCs, was identified as the formal product of an intramolecular esterification of the propionate and primary glucopyranosyl hydroxyl groups of Ug‐NCC‐43. Thus, the glucopyranose moiety and three of the pyrrole units of Ug‐NCC‐53 span a 20‐membered ring, installing a bicyclo[17.3.1]glycoside moiety. This structural motif is unprecedented in heterocyclic natural products, according to a thorough literature search. The remarkable, three‐dimensional bicyclo[17.3.1]glycoside architecture reduces the flexibility of the linear tetrapyrrole. This feature of Ug‐NCC‐53 is intriguing, considering the diverse biological effects of known bicyclo[n.3.1]glycosidic natural products.